1997
DOI: 10.1037/0882-7974.12.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping of older adults: The role of target facial cues and perceiver characteristics.

Abstract: This 2-part study used photograph-age and photograph-stereotype sorting tasks to examine the role of target facial cues in stereotyping of older persons. As predicted, young, middle-aged, and older participants associated photographs of those who looked older and those with a neutral facial expression with fewer positive stereotypes than other photographs. Participants also selected fewer positive stereotypes for photographs of women than of men, except when the photographs showed old-old (80 years and over) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 33 publications
5
83
1
2
Order By: Relevance
“…There is conflicting evidence regarding the influence of gender differences with respect to sensitivity to age differences. While some studies (Snyder & Miene, 1994) report that women are more likely to stereotype older adults than men, most studies find no gender effects (Hummert, Garstka, & Shaner, 1997). In addition we control for education as managers from different educational levels might have a different perceptions of older workers' productivity.…”
Section: Theory Of Age Stereotypesmentioning
confidence: 99%
“…There is conflicting evidence regarding the influence of gender differences with respect to sensitivity to age differences. While some studies (Snyder & Miene, 1994) report that women are more likely to stereotype older adults than men, most studies find no gender effects (Hummert, Garstka, & Shaner, 1997). In addition we control for education as managers from different educational levels might have a different perceptions of older workers' productivity.…”
Section: Theory Of Age Stereotypesmentioning
confidence: 99%
“…Although gender stereotypes have been well established in the human-computer interaction literature, evidence suggests that technology can also be vulnerable to aging stereotypes . Physical appearance, facial features, and perceived age are known to play a role in the activation of age stereotypes (Hummert, Garstka, & Shaner, 1997). Age is one of the first and most salient attributes we notice about other people (Fiske, Kitayama, Markus, & Nisbett, 1998), which may also be true of other anthropomorphic technology such as robots.…”
Section: Methodsmentioning
confidence: 99%
“…The link between physical characteristics and stereotypes has been well established in the social cognition literature (Brewer & Lui, 1984;Hummert, Garstka, & Shaner, 1997). Within this context, facial features are considered to be the main source of information used in order to activate stereotypes.…”
Section: Stereotypes and Agingmentioning
confidence: 99%
“…Hummert et al (2004), in their excellent review of the role of age stereotypes in communication, cited numerous studies that provide support for the ASI model. Investigations by Hummert (2002), Bieman-Copland andRyan (2001), Mulac and Giles (1996), Harwood and Williams (1996), Hummert, Garstka, and Shaner (1997), Ryan, Kennaley, Pratt, and Shumovich (2000), Thimm, Rademacher, and Kruse (1998), and others have shown that both positive and negative stereotypes are activated by an encounter with an older target. This activation then leads to stereotypic beliefs about the older adult's communicative competencies that are consistent with the stereotype's valence.…”
Section: Communication Predicament and Enhancement Models Of Agingmentioning
confidence: 99%